Melatonin Improves Cotton Salt Tolerance by Regulating ROS Scavenging System and Ca2 + Signal Transduction - Zhang, Yuexin; Fan, Yapeng; Rui, Cun; Zhang, Hong; Xu, Nan; Dai, Maohua; Chen, Xiugui; Lu, Xuke; Wang, Delong; Wang, Junjuan; Wang, Jing; Wang, Qinqin; et al. (Frontiers in Plant Science, 2021)
As one of the crash crops, cotton is facing the threat of abiotic stress during its growth and development. It has been reported that melatonin is involved in plant defense against salt stress, but whether melatonin can improve cotton salt tolerance and its molecular mechanism remain unclear. We investigated the role of melatonin in cotton salt tolerance by silencing melatonin synthesis gene and exogenous melatonin application in upland cotton. Results: We found that application of melatonin can improve salt tolerance of cotton seedlings. The content of endogenous melatonin was different in cotton varieties with different salt tolerance. To explore the protective mechanism of exogenous melatonin against salt stress by RNA-seq analysis. The inhibition of melatonin biosynthesis related genes and endogenous melatonin content in cotton resulted in the decrease of antioxidant enzyme activity, Ca2+ content and salt tolerance of cotton. Conclusion: Melatonin played an important role in the resistance of cotton to salt stress, improved the salt tolerance of cotton by regulating antioxidant enzymes, transcription factors, plant hormones, signal molecules and Ca2+ signal transduction. This study proposed a regulatory network for melatonin to regulate cotton's response to salt stress, which provided a theoretical basis for improving cotton's salt tolerance.